Ultrasound markers informative of efficient non-pharmacological correction of hypofibrinolysis at preconception period in patients with recurrent pregnancy loss - E. I. Lebedeva; S. D. Yavorskaya; A. P. Momot; N. I. Fadeeva (Фундаментальная и клиническая медицина, 2021)
Aim. To find reliable ultrasound markers of efficient non-pharmacological correction of hypofibrinolysis at preconception period in patients with recurrent pregnancy loss.Materials and Methods. We conducted a single-center, prospective, non-randomized study in patients with recurrent pregnancy loss and hypofibrinolysis (n = 120), who received intermittent pneumatic compression during preconception care. During the pregnancy, we performed a comprehensive 3D ultrasound examination of the endometrium and corpus luteum in the VOCAL mode. Then, we compared patients with (n = 97) and without (n = 23) favorable outcome. Predictive power of the ultrasound parameters was evaluated by a calculation of the area under the receiver operating characteristic (ROC) curve (AUC) and ROC curve comparison.Results. Vascularization flow index of endometrial perfusion (AUC = 0.566) and corpus luteum (AUC = 0.639) was identified as a potential marker of efficient intermittent pneumatic compression at preconception period.Conclusions. Adequate perfusion of endometrium and corpus luteum, reflected by vascularization flow index, may indirectly indicate successful trophoblast invasion and minimize the risk of recurrent pregnancy loss.